A sRNA in a reduced mutualistic symbiont genome regulates its own gene expression. Issue 8 (2nd December 2017) - Thairu, Margaret W.; Cheng, Siyuan; Hansen, Allison K.
Abstract: Similar to other nutritional endosymbionts that are obligate for host survival, the mutualistic aphid endosymbiont, Buchnera, has a highly reduced genome with few regulatory elements. Until recently, it was thought that aphid hosts were primarily responsible for regulating their symbiotic relationship. However, we recently revealed that Buchnera displays differential protein regulation, but not mRNA expression. We also identified a number of conserved small RNAs (sRNAs) that are expressed among Buchnera taxa. In this study, we investigate whether differential protein regulation in Buchnera is the result of post‐transcriptional gene regulation via sRNAs. We characterize the sRNA profile of two Buchnera life stages: (i) when Buchnera is transitioning from an extracellular proliferating state in aphid embryos and (ii) when Buchnera is in an intracellular nonproliferating state in aphid bacteriocytes (specialized symbiont cells). Overall, we identified 90 differentially expressed sRNAs, 97% of which were upregulated in aphid embryos. Of these sRNAs, the majority were predicted to be involved in the regulation of various metabolic processes, including arginine biosynthesis. Using a heterologous dual expression vector, we reveal for the first time that a Buchnera antisense sRNA can post‐transcriptionally interact with its cognate Buchnera coding sequence, carB, a gene involved in arginine biosynthesis. These results corroborate our in vivo RNAseq and proteomic data, where the candidate antisense sRNA carB and the protein CarB are significantly upregulated in aphid embryos. Overall, we demonstrate that Buchnera may regulate gene expression independently from its host by utilizing sRNAs.